2020
DOI: 10.1515/rams-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic degradation study of PLA-based composite scaffolds

Abstract: Disadvantages in the use of polylactic acid (PLA) as a base material for Tissue Engineering applications include the low osteoconductivity of this biomaterial, its acidic degradation and the deficient cellular adhesion on its surface. In order to counteract these drawbacks, calcium carbonate (CaCO3) and β-tricalcium phosphate (Ca3(PO4)2, β-TCP) were proposed in this work as additives of PLA-based support structures. Composite scaffolds (PLA:CaCO3: β-TCP 95:2.5:2.5) manufactured by fused deposition modeling (FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…According to Zhuikov et al, (2021) [27], enzymatic degradation is found to significantly accelerate the degradation rate of PLA I PHB compared to non-enzymatic hydrolytic degradation. The first reported PLA-degrading enzyme was proteinase K from Tritirachium album [28,29]. Chemical modification of packaging materials is not always a preferred strategy in pollutant management and remediation as it may inhibit degradation by acting on the cells of microorganisms and their enzymes, particularly if the substance is of a strong biocidal nature and shows inhibitory activity towards biocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…According to Zhuikov et al, (2021) [27], enzymatic degradation is found to significantly accelerate the degradation rate of PLA I PHB compared to non-enzymatic hydrolytic degradation. The first reported PLA-degrading enzyme was proteinase K from Tritirachium album [28,29]. Chemical modification of packaging materials is not always a preferred strategy in pollutant management and remediation as it may inhibit degradation by acting on the cells of microorganisms and their enzymes, particularly if the substance is of a strong biocidal nature and shows inhibitory activity towards biocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, Donate et al have proposed calcium carbonate (CaCO 3 ) and β-tricalcium phosphate (Ca 3 (PO 4 ) 2 , β-TCP) as additives in PLA structures. The composite scaffolds were manufactured by fused de-position modeling (FDM) and tested under enzymatic degradation, demonstrating an increased degradation rate [ 60 ]. 3D-printed porous composite scaffolds made of polylactic acid (PLA)/hydroxyapatite (HAP) with a content of ceramic material above 20 wt/wt% were developed through FDM by Bernardo et al and obtained mechanical performances similar to those of the trabecular bone.…”
Section: Biomaterials For Bone Tissue Engineering: the Progress Of Th...mentioning
confidence: 99%
“…Properties of PLA inks for solvent-cast printing of three-dimensional freeform microstructures [39]- [41]. It is semi-crystalline, biocompatible, and has found use in several medical applications like orthopedic implants, drug delivery systems, and bio-fabrication [38], [42]. The semi-crystalline morphology increases mechanical integrity.…”
Section: Less Flexibilitymentioning
confidence: 99%